2017
DOI: 10.1515/peps-2017-0010
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Farmer-Pastoralist Violence on State-Level Internal Revenue Generation in Nigeria: A Modified Synthetic Control Analysis Approach

Abstract: Nigeria’s ethnically and religiously diverse Middle Belt has experienced recurrent eruptions of violence over the past several decades. Disputes between pastoralists and farmers arise from disagreements over access to farmland, grazing areas, stock routes, and water points for both animals and households. Although relatively low in intensity, this form of violence is widespread, persistent, and arguably increasing in its incidence. This study seeks to answer the question: How has farmer-pastoralist conflict af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…When he claimed in the quote (#7-EggNas-M) that nobody was killed, I was sceptical because there were numerous reports on the internet about killings in the EH community during that time. In a research study conducted in 2017, Mcdougal, Hagerty and Dowd (2018) identified the 'EH Communal Militia' as one of the key participants in the conflict commonly referred to as the 'farmer-pastoralist conflict', now more accurately characterised as eco-violence. Thus, the O and GD people firmly believe in their obligation to recover and safeguard their ancestral territory.…”
Section: The Role Of Collective Memory In Shaping Immobility In the M...mentioning
confidence: 99%
“…When he claimed in the quote (#7-EggNas-M) that nobody was killed, I was sceptical because there were numerous reports on the internet about killings in the EH community during that time. In a research study conducted in 2017, Mcdougal, Hagerty and Dowd (2018) identified the 'EH Communal Militia' as one of the key participants in the conflict commonly referred to as the 'farmer-pastoralist conflict', now more accurately characterised as eco-violence. Thus, the O and GD people firmly believe in their obligation to recover and safeguard their ancestral territory.…”
Section: The Role Of Collective Memory In Shaping Immobility In the M...mentioning
confidence: 99%